Enzymatic synthesis of L-theanine from L-glutamine and ethylamine by Bacillus licheniformis γ-glutamyltranspeptidase and its mutants specialized in transpeptidase activity. (November 2019) - Chi, Meng-Chun; Lin, Min-Guan; Huang, Yu-Fen; Chen, Yi-Yu; Wang, Tzu-Fan; Lin, Long-Liu
Abstract: In this investigation, Bacillus licheniformis γ-glutamyltranspeptidase ( Bl GGT) together with its two transpeptidase-specialized mutants (N450D and N450Q) were employed for the biocatalytic synthesis of L -theanine. A high-pressure liquid chromatographic method coupled with ultraviolet detection (HPLC/UV) was used to quantify L -theanine content in the reaction mixture. Through a series of experiments, the perfect conditions for the biocatalytic synthesis were found to be an operational pH of 10.5, a reaction time of 4 h, L -glutamine and ethanolamine in a 1:2.4 M ratio, and enzymes at a working concentration of 25 μg/mL. In a batch process for N450D-mediated synthesis of L -theanine at 37 °C, a conversion rate of ~94% was achieved from 250 mM l -glutamine and 600 mM ethylamine. Successful synthesis of the desired product was further verified by mass spectrometry analysis. Conclusively, the experimental results suggest a high potential application in the production of L -theanine by Bl GGT-mediated biocatalysis.